PERBAIKAN KUALITAS CITRA MAPS MENGGUNAKAN METODE CONTRAST LIMITED ADAPTIVE HISTOGRAM EQUALIZATION (CLAHE) - Dian Lestari Nasution (STMIK Budi Darma, 2019)
Map images that are on Google Maps can also be screenshooted, when taking image maps / maps the image quality is not optimal, this is because the ability of the computer used to take the image does not support high graphics. This map image can be used as material for the purposes of work that uses images such as graphic design, namely printing.The ability of computers that do not support large graphics processing in getting a good image is not a major problem in image improvement. Because the image that is not maximized, its color elements can be manipulated with digital image processing techniques, one of the methods for manipulating elements of image colors is the CLAHE method. The CLAHE method is applied and calculates the pixel values that exist in each RGB layer. In the field of graphic design images that have less intensity can be improved by increasing contrast. Image contrast enhancement can be done by the CLAHE method.Keywords: Maps Imagery, Contrast, CLAHE